A Rise of TLP (Tehreek-e-Labbaik Pakistan) and Barelvi Sect in Pakistan’s Political and Social Arena - Ijaz, Sabir (Annals of Human and Social Sciences, 2025)
The aim of the paper is to exclusively explain the politicization of the TLP and Barelvi sect in Pakistan. It explains how the sect associates itself with the teaching of syncretic Sufism which is peaceful and tolerant. Historically, the sect has remained peaceful with no political participation; however, recently under the tutelage of TLP the sect has started showing assertiveness through various audacious acts. One of Barelvis late clerics, Khadim Hussian Rizvi the founder of TLP, has openly provoked even policemen and other followers to kill the blasphemers. Such statements are very sensitive. It is a qualitative study. The study has mainly included books, scholarly journals and newspapers for discussion. The aggressive statements and protests by TLP can start a new wave of sectarianism. The party demand of the death of anyone who commits blasphemy might undermine social balance. It is recommended that government must ensure justice for all the individuals including minorities. No one should be exempted from deteriorating law and order situation in the country.